2015
DOI: 10.1103/physrevb.92.174512
|View full text |Cite
|
Sign up to set email alerts
|

Bulk disorder in the superconductor affects proximity-induced topological superconductivity

Abstract: We investigate effects of ordinary nonmagnetic disorder in the bulk of a superconductor on magnetic adatom-induced Shiba states and on the proximity-induced superconductivity in a nanowire tunnel-coupled to the bulk superconductor. Within the formalism of self-consistent Born approximation we show that, contrary to the widespread belief, the proximity-induced topological superconductivity can be adversely affected by the bulk superconducting disorder even in the absence of any disorder in the nanowire (or the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
55
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(59 citation statements)
references
References 77 publications
3
55
1
Order By: Relevance
“…This is remarkable, especially considering the dramatic disorder vulnerability of the Yu-Shiba-Rusinov (YSR) states [28][29][30] created by single magnetic impurity. 24 More specifically, by performing self-consistent calculations also taking into account the effect of disorder on the superconducting state, we find that the MBS exist and are stable as long as the surrounding (conventional s-wave) SC shows only moderate signs of inhomogeneity. Thus simply measuring the local density of states (LDOS) in the surrounding SC gives a very good prediction of the MBS disorder stability.…”
Section: -8mentioning
confidence: 86%
See 1 more Smart Citation
“…This is remarkable, especially considering the dramatic disorder vulnerability of the Yu-Shiba-Rusinov (YSR) states [28][29][30] created by single magnetic impurity. 24 More specifically, by performing self-consistent calculations also taking into account the effect of disorder on the superconducting state, we find that the MBS exist and are stable as long as the surrounding (conventional s-wave) SC shows only moderate signs of inhomogeneity. Thus simply measuring the local density of states (LDOS) in the surrounding SC gives a very good prediction of the MBS disorder stability.…”
Section: -8mentioning
confidence: 86%
“…They also have the added benefit of keeping the effective chemical potential constant in the whole sample, which leads to better control of the topological phase. For comparison we here also report results for a single type of impurity, such that the chemical potential is changed by a fixed amount δµ i = w, but only on randomly selected sites with a fixed disorder concentration n. This type of disorder has been considered for topological superconducting nanowires 24 but not, to the best of our knowledge, for magnetic impurity chains deposited on a superconducting surface. Figure 11 show the results for two chains W 18 and W 28 using the same parameters as in Fig.…”
Section: Single Impurity Disordermentioning
confidence: 99%
“…There has been significant discussion of the importance of treating the parent superconductor explicitly when analyzing the proximity effect theoretically, as the proximity coupling can strongly renormalize the bulk properties of the nanowire. 28,[41][42][43][44][45][46][47][48][49] As the experimentally achievable coupling strength continues to increase, it becomes more important to understand the effect of the parent superconductor on the transport properties of the nanowire as well.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, it was suggested that disorder in the underlying superconductor may lead to variation in this parameter [36]. In addition, variation of the exchange coupling J , originating from different microscopic coupling configurations between the atom and the substrate, will also translate into variation of α.…”
Section: A Topological Properties Of Disordered Chainsmentioning
confidence: 99%
“…Since the early work on the subject [30][31][32][33], the effects of disorder in the nanowire systems [34] and Kitaev's toy model [35] have been studied extensively. However, the special properties of magnetic chains have received relatively little attention [36,37].…”
Section: Introductionmentioning
confidence: 99%